Pharmacokinetic properties of a once-daily formulation of tacrolimus in patients with renal transplantation - Imanishi, Yoshinori; Matsui, Kumi; Ishida, Kenichiro; Ito, Shin-ichi; Matsuura, Katsuhiko; Deguchi, Takashi; Itoh, Yoshinori (Arzneimittelforschung, 2011)
The present study was designed to determine the pharmacokinetic profiles of a once-daily formulation of tacrolimus (CAS 104987-11-3; TAC-once) in patients before and after introduction of renal transplantation. Pharmacokinetic parameters for tacrolimus were almost comparable among patients receiving TAC- once before, 2 weeks after and 3 weeks after renal transplantation. Among various parameters, Ctrough correlated most closely with the area under the concentration-time curve during 24 h (AUC0–24) (R2 = 0.82, P < 0.001), while no consistent correlation was observed between AUC0–24 and concentrations at 2 h or 4 h, or the dose of TAC-once. The clinical outcomes such as the incidence of acute rejection, renal tissue injury and cytomegalovirus infection were evaluated during the first 3 weeks and 3 months after transplantation, and the data were compared with the historical data obtained from patients who had received the conventional twice-daily formulation of tacrolimus (TAC-twice). There were no significant differences in the incidence of such clinical outcomes between the two groups. These findings suggest that Ctrough is useful for therapeutic monitoring of tacrolimus in patients receiving TAC-once. In addition, pharmacokinetics and clinical outcomes were comparable between TAC-once and TAC-twice formulations.
Keywords: Area under the concentration-time curve; CAS 104987-11-3; Pharmacokinetics; Renal transplantation; Tacrolimus, once-daily formulation; Trough concentration